"I Would Like for My Child to be Happy with His Life": Parental Hopes for Their Children with ASD Across the Lifespan. - Finke, Erinn H.; Kremkow, Jennifer M. D.; Drager, Kathryn D. R.; Murillo, Angelique; Richardson, Laura; Serpentine, Elizabeth C. (Journal of Autism & Developmental Disorders, 2019)
The purpose of this project was to understand the hopes of parents with children with ASD. Particularly understudied are the hopes parents have for long-term outcomes for their child. A cross-sectional focus group design was used and six focus groups were completed. These groups included parents of (1) preschool aged children who were recently diagnosed, (2) children in early elementary school, (3) children in later elementary school, (4) children in middle school, (5) children in high school, and (6) children who are adults with ASD. Results indicated 77.4% of the data were devoted to hopes for the children's independence, happiness, and skill improvement; increased authentic socially significant relationships; and future employment.